Shared Pain: Lessons from the Labour Room in Istanbul - Patricia K Morley-Forster (Pain Research and Management)
The current issue of Pain Research & Management contains an article by Yildirim and Sahin (pages 183-187) from the Faculty of Nursing at the University of Istanbul (Istanbul, Turkey). At first glance, this paper appears to be of interest only to those involved in the day-to-day care of women in labour, but a closer look reveals significant lessons for those dedicated to the improvement of pain management globally.